Synthetic earthquake catalogs simulating seismic activity in the Corinth Gulf, Greece, fault system. Issue 1 (25th January 2015) - Console, Rodolfo; Carluccio, Roberto; Papadimitriou, Eleftheria; Karakostas, Vassilis
Abstract The characteristic earthquake hypothesis is the basis of time‐dependent modeling of earthquake recurrence on major faults. However, the characteristic earthquake hypothesis is not strongly supported by observational data. Few fault segments have long historical or paleoseismic records of individually dated ruptures, and when data and parameter uncertainties are allowed for, the form of the recurrence distribution is difficult to establish. This is the case, for instance, of the Corinth Gulf Fault System (CGFS), for which documents about strong earthquakes exist for at least 2000 years, although they can be considered complete for M ≥ 6.0 only for the latest 300 years, during which only few characteristic earthquakes are reported for individual fault segments. The use of a physics‐based earthquake simulator has allowed the production of catalogs lasting 100, 000 years and containing more than 500, 000 events of magnitudes ≥ 4.0. The main features of our simulation algorithm are (1) an average slip rate released by earthquakes for every single segment in the investigated fault system, (2) heuristic procedures for rupture growth and stop, leading to a self‐organized earthquake magnitude distribution, (3) the interaction between earthquake sources, and (4) the effect of minor earthquakes in redistributing stress. The application of our simulation algorithm to the CGFS has shown realistic features in time, space, and magnitude behavior of the seismicity. These features include long‐term periodicity of strong earthquakes, short‐term clustering of both strong and smaller events, and a realistic earthquake magnitude distribution departing from the Gutenberg‐Richter distribution in the higher‐magnitude range.